Aggregation-induced emission-active hyperbranched polymers conjugated with tetraphenylethylene for nitroaromatic explosive detection. (October 2021) - Kalva, Nagendra; Tran, Chinh Hoang; Lee, Min Woong; Augustine, Rimesh; Lee, Soo Jeong; Kim, Il
Abstract: This work develops a facile synthesis for aggregation-induced emission (AIE)-active hyperbranched polyglycidols (HPGs) to design a solid-state sensor for detecting nitroaromatic explosives. The tetraphenylethylene moieties were conjugated onto the periphery of the HPGs in a single step using dynamic boronate ester cross-linkers. The resulting AIE-active HPGs exhibited excellent AIE characteristics in tetrahydrofuran (THF)/H2 O mixtures, emitting a strong blue fluorescence under UV irradiation. Dynamic light scattering and transmission electron microscopic analyses demonstrated that the self-assembled nanosized aggregates were stable in the THF/H2 O mixture. The fluorescence of the aggregates was dramatically quenched by various nitro compounds, including 2, 4, 6-trinitrophenol (or picric acid; PA), 2, 6-dinitrophenol, 4-nitrophenol, 4-nitrotoluene, and nitromethane. The nano-aggregates exhibited extraordinary sensitivity towards PA, with a Stern‒Volmer constant (Ksv ) of 2.27 × 10 4 M −1 and a limit of detection of 40 ppb. Paper strips encapsulating the aggregates exhibited a vivid visual quenching, promising the practical applicability of these polymers as solid-state sensors for the detection of nitroaromatic explosives. Graphical abstract: Image 1